Understanding Gluten Sensitivity and Celiac Disease - Stephanie Meyer; Karla P. Shelnutt; Gail P. Kauwell (EDIS, 2013)
Several years ago, most people probably had never heard of gluten, but by 2011, gluten-free diets became more popular than low carbohydrate diets. One reason for this is the increased awareness and diagnosis of conditions in which gluten triggers an abnormal response in the body, such as gluten sensitivity and celiac disease. This 4-page fact sheet will help you learn about gluten sensitivity and celiac disease, as well as understand what they have in common and what is different about them. Written by Stephanie Meyer, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family Youth and Community Sciences, April 2013.